PERTUMBUHAN, PRODUKSI SIMPLISIA, DAN KANDUNGAN FENOLIK TOTAL SELASIH (Ocimum basilicum L.) PADA BERBAGAI TARAF CEKAMAN KEKERINGAN DAN WAKTU PANEN - Buchory, Gina Nuraini; Anwar, Syaiful; Kristanto, Budi Adi (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2021)
Basil (Ocimum basilicum L.) is an aromatic plant that is known for its spice and medicinal benefits that valued mainly for its fresh and dry leaves (simplicia/crude drugs). This study aimed to evaluate growth, simplicia production, and total phenolic content of basil under different levels of drought stress and harvest time. The experiment was conducted at The Greenhouse of Plant Breeding and Physiology Laboratory Faculty of Animal Science and Agriculture Diponegoro University. The research was using a completely randomized design (RAL) consisting of two factors 3x3 with 3 replication. Drought stress treatments in field capacity included : K1 (100% FC), K2 (75% FC), and K3 (50% FC) as the first factor. Harvest time treatments included : W1 (5 Weeks After Planting), W2 (6 Weeks After Planting), and W3 (7 Weeks After Planting) as the second factor. Parameters evaluated were root volume, plant height, total leaf area, simplicia production, and total phenolic content. Analysis of Variance (ANOVA) and Tukey test (pâ‰¤0,05%) were carried out to determine significant different between treatments and interactions. Results indicated that: (a) drought stress treatments significantly reduced growth and production of basil plant simplicia, but it did not provide a significant difference in the total phenolic content; (b) the harvest time treatment increased growth and production of basil plant simplicia, and decreased total phenolic content significantly; and (c) there were interactions between drought stress treatments and harvest time treatments.